IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING FREE POETRY THROUGH THE REAL EXPERIENCE METHOD IN CLASS IV STUDENTS OF MADRASAH IBTIDAIYAH NEGERI 1 WEST ACEH ACADEMIC YEAR 2022/2023 - Risnawati, Cut; Lidan, M (LUMBUNG AKSARA, 2022)
This study aimed to determine "The improvement of Students’ Achievement in Writing Free Poetry through the Real Experience Method in Grade IV Students of Madrasah Ibtidaiyah Negeri 1 West Aceh, Academic Year 2022/2023". The research sample was Grade IV students with the total number of students was 25 students. This study used a Classroom Action Research with the method of observation, data collection, test, documentation and data analysis. This study used two cycles to find out the improvement of students’ achievement in writing free poetry through the Real Experience Method in Grade IV students of Madrasah Ibtidaiyah Negeri 1 West Aceh, Academic Year 2022/2023. The results of this study indicated that the Real Experience Method can improve the achievement of Grade IV students of Madrasah Ibtidaiyah Negeri 1 West Aceh. It could be seen from the results of learning in the pre-cycle, cycle I and II. As for students’ achievement in the pre-cycle, there were only 8 students (32%) who reached the passing grade, in cycle I, it went up into 17 students (68%) and 25 students (100%) who reached the passing grade in cycle II.